A concrete additive and high-strength concrete prepared by the same

By using modified polycarboxylic acid water reducing agent and composite rust resistor in concrete additives, the corrosion problems caused by chloride ions in reinforced concrete structures are solved, and the rust resistance performance and compressive strength are significantly improved, and the service life of the steel bars is extended.

CN118851615BActive Publication Date: 2025-03-25NANJING TENGHENG NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411085010.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-08
Publication Date
2025-03-25
Estimated Expiration
2044-08-08

AI Technical Summary

Technical Problem

Corrosion problems caused by chloride ions in reinforced concrete structures lead to corrosion of steel bars, reduced structural strength and potential structural collapse.

Method used

A concrete additive is developed, including modified polycarboxylic acid water reducer, sodium dodecyl sulfonate and composite rust inhibitor. The quaternary ammonium corrosion inhibitor with biimidazoline structure is added during the preparation process of the modified polycarboxylic acid water reducer, and the rust inhibitor is grafted through free radical polymerization to improve compatibility and dispersion.

Benefits of technology

It significantly improves the rust resistance and compressive strength of concrete, extends the service life of steel bars, and avoids the poor water solubility and dispersion problems of traditional rust resistors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of concrete additives, and discloses a concrete additive and a high-strength concrete prepared by the same. A concrete additive comprises the following components in parts by weight: 15-30 parts of a modified polycarboxylic acid water-reducing agent, 5-10 parts of sodium dodecyl sulfate, 1-10 parts of a composite rust inhibitor, and 50-60 parts of water. A high-strength concrete comprises the following components in parts by weight: 20-30 parts of cement, 100-120 parts of coarse aggregate, 60-65 parts of fine aggregate, 10-15 parts of fly ash, 15-25 parts of water, and 1-10 parts of a concrete additive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete additives, in particular to a concrete additive and high-strength concrete prepared therefrom. Background Art

[0002] Reinforced concrete is the most widely used building material in the construction industry. The good properties of concrete components provide a prerequisite for good physical and chemical protection of embedded reinforcements from corrosive environments. However, reinforcement corrosion remains a serious threat and a major durability degradation issue. It is closely associated with structural failures, economic losses and catastrophic events. Chloride attack is one of the main causes of reinforcement corrosion in reinforced concrete structures, considering marine environments and offshore exposure or de-icing salt application in cold and snowy areas.

[0003] Rebar corrosion not only causes cracking and spalling, but also reduces the cross-sectional area of ​​the steel bar, resulting in a decrease in the strength of reinforced concrete. Ultimately, reinforced concrete structures deteriorate or even collapse. Therefore, it is imperative to find environmentally friendly and effective ways to deal with the problem of steel bar corrosion to prevent premature damage and extend its service life. For decades, steel bar corrosion has been a problem that has plagued experts and scholars around the world. As mentioned earlier, in a concrete environment, steel bar corrosion occurs when the chloride ion content on the surface of the steel bar reaches a certain threshold. Chloride ions act as a catalyst to depassivate the steel bar without changing the overall pH value. Then, it causes pitting and local acidification of the steel bar. Chloride ions in reinforced concrete exist mainly in two forms. One is called bound chloride ions and the other is called free chloride ions. Since free chloride ions are a necessary factor in initiating steel bar corrosion, this article pays special attention to corrosion caused by free chloride ions. Carbon steel rebar is the most commonly used metal material in reinforced concrete structures. It can withstand large loads and has the characteristics of high tensile strength. As an important step to prevent the corrosion of carbon steel rebar, Fe on the surface of the rebar undergoes an oxidation-reduction reaction to form a protective film called a passivation film. However, chloride attack can destroy the passive film on carbon steel bars, leading to structural damage.

[0004] Therefore, it is of great significance to invent a concrete additive to prevent the corrosion of carbon steel reinforcing bars. Summary of the invention

[0005] The object of the present invention is to provide a concrete additive and high-strength concrete prepared therefrom, so as to solve the problems raised in the above-mentioned background technology.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] A concrete additive comprises the following components in parts by weight: 15-30 parts of a modified polycarboxylic acid water-reducing agent, 5-10 parts of sodium dodecyl sulfonate, 1-10 parts of a composite rust inhibitor, and 50-60 parts of water.

[0008] Furthermore, the preparation method of the modified polycarboxylate water-reducing agent comprises the following steps:

[0009] S1: Add epoxidized oleic acid and hydroxyethylethylenediamine to xylene and stir evenly, heat to 150-155°C to react for 4-4.5h, heat to 220-225°C to react for 4-4.5h, cool to 110-115°C, remove unreacted raw materials and xylene by vacuum distillation to obtain intermediate A; add acrylated oleic acid and hydroxyethylethylenediamine to xylene and stir evenly, heat to 150-155°C to react for 4-4.5h, heat to 220-225°C to react for 4-4.5h, cool to 110-115°C, remove unreacted raw materials and xylene by vacuum distillation to obtain intermediate B;

[0010] S2: Add intermediate A, intermediate B and dichloromethane to anhydrous ethanol and stir evenly, heat to 80-85°C and reflux for reaction for 4-4.5 hours, remove the solvent by distillation under reduced pressure, add acetone for recrystallization and purification, and obtain a bisimidazoline quaternary ammonium salt;

[0011] S3: Add acrylic acid and diimidazole quaternary ammonium salt into deionized water and ultrasonically dissolve them to obtain solution A; add ascorbic acid and thioglycolic acid into deionized water and ultrasonically dissolve them to obtain solution B; add methyl allyl polyoxyethylene ether into deionized water, heat to 70-75°C, stir until methyl allyl polyoxyethylene ether is dissolved, add hydrogen peroxide, stir for 10-15 minutes, and simultaneously add solution A and solution B dropwise, keep warm for 1-1.5 hours, adjust the pH to 6-8 with 40wt% sodium hydroxide solution, continue stirring for 20-30 minutes, and cool to room temperature to obtain a modified polycarboxylic acid water reducer.

[0012] Furthermore, the method for preparing acrylated oleic acid comprises the following steps:

[0013] Add epoxidized oleic acid, acrylic acid, and hydroquinone into a reaction vessel and stir evenly, heat to 100-105°C and reflux for reaction for 6-6.5 hours, add ether solution, stir for 15-30 minutes, remove the aqueous phase, wash the organic phase with saturated sodium bicarbonate solution until neutral, add anhydrous sodium sulfate, filter, and remove ether by rotary evaporation to obtain acrylic oleic acid;

[0014] Furthermore, in the acrylated oleic acid, the mass ratio of epoxidized oleic acid to acrylic acid is 1:2; and the amount of hydroquinone added is 0.6-0.8 mg per 1 g of acrylic acid.

[0015] Furthermore, the preparation method of the epoxidized oleic acid comprises the following steps:

[0016] Add oleic acid and formic acid to toluene and stir evenly, add hydrogen peroxide, heat to 80-85°C and reflux for reaction for 2.5-3h, add 10wt% sodium bisulfite, stir for 15-30min, remove the aqueous phase, wash the organic phase with deionized water, add anhydrous sodium sulfate, filter, and remove the solvent by rotary evaporation to obtain epoxidized oleic acid;

[0017] Furthermore, in the epoxidized oleic acid, the molar ratio of oleic acid:formic acid:hydrogen peroxide is (1-2):(2-4):(20-40).

[0018] Furthermore, in the intermediate A, the molar ratio of epoxidized oleic acid:hydroxyethylethylenediamine is 1:1.2; in the intermediate B, the molar ratio of acrylated oleic acid:hydroxyethylethylenediamine is 1:1.2; in the bisimidazoline quaternary ammonium salt, the molar ratio of intermediate A:intermediate B:dichloromethane is 1:1:1.

[0019] Furthermore, in the polycarboxylate water-reducing agent, the molar ratio of methyl allyl polyoxyethylene ether: acrylic acid: diimidazole quaternary ammonium salt: thioglycolic acid: hydrogen peroxide: ascorbic acid is 1:(3-4):(1-1.4):(0.18-0.36):(0.014-0.017):(0.01-0.02).

[0020] Furthermore, the preparation method of the composite rust inhibitor comprises the following steps:

[0021] Step (1): adding intermediate B to a reaction vessel, adding potassium hydroxide catalyst, sealing the reaction vessel, introducing a portion of ethylene oxide until the pressure in the reaction vessel reaches 0.2-0.21 MPa, heating to 120-130° C. for reaction, continuously adding the remaining ethylene oxide during the reaction, maintaining the pressure and temperature in the reaction vessel stable during the reaction, and aging for 30-45 minutes after the reaction is completed to obtain an imidazoline macromonomer;

[0022] Step (2): under a nitrogen atmosphere, add imidazoline macromonomer and styrene to toluene and stir evenly, add boron trifluoride-ether complex, heat at 20-22°C to carry out polymerization reaction for 24-48 hours, wash the product with heptane, and vacuum dry to obtain an amphiphilic block copolymer;

[0023] Step (3): Add the amphiphilic block copolymer and sodium molybdate into 1,4-dioxane and stir for 4-5 hours, place the solution in a dialysis bag and seal it, and place the dialysis bag in a sodium molybdate solution for dialysis to obtain a composite rust inhibitor.

[0024] Furthermore, the preparation method of the intermediate B in the composite rust inhibitor is the same as the preparation method of the intermediate B in the modified polycarboxylic acid water reducer.

[0025] Furthermore, in the imidazoline macromonomer, the molar ratio of intermediate B to ethylene oxide is 1:60. The amount of potassium hydroxide added is 0.3-0.4% of the mass of intermediate B.

[0026] Furthermore, in the amphiphilic block copolymer, the mass ratio of imidazoline macromonomer:styrene is (1-2):4.5; in the composite rust inhibitor, the mass ratio of amphiphilic block copolymer:sodium molybdate is 2.5:(4.5-5).

[0027] Furthermore, the concentration of the sodium molybdate solution is 1 g / L; during the dialysis process, the sodium molybdate solution is replaced every 1 hour, the dialysis is performed 8 times and the last dialysis is performed overnight; the ultrapure water dialysis is replaced, the ultrapure water is replaced every 1 hour, the dialysis is performed 8 times and the last dialysis is performed overnight; the amount of the boron trifluoride-ether complex added is 0.2-0.5% of the mass of the imidazoline macromonomer.

[0028] A high-strength concrete comprises the following components by weight: 20-30 parts of cement, 100-120 parts of coarse aggregate, 60-65 parts of fine aggregate, 10-15 parts of fly ash, 15-25 parts of water and 1-10 parts of concrete additives.

[0029] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0030] The invention prepares self-made acrylated oleic acid by sequentially performing epoxidation and acrylate treatment on oleic acid, and then prepares intermediate B with an imidazoline structure by performing amidation reaction between acrylated oleic acid and hydroxyethylethylenediamine. Intermediate B is used as a basic raw material and is respectively involved in the preparation process of modified polycarboxylic acid water reducer and composite rust inhibitor. The compatibility and dispersibility of water reducer and rust inhibitor in concrete additives are greatly improved, and the problem that traditional water reducer and rust inhibitor are easy to agglomerate in concrete and have poor dispersibility is solved.

[0031] The intermediates A and B are prepared by amidation reaction of epoxidized oleic acid and hydroxyethylethylenediamine, and are used as raw materials to react with quaternary ammonium reagent 1,6-dichlorohexane to prepare a quaternary ammonium salt corrosion inhibitor with a bisimidazoline structure. The quaternary ammonium salt is used as a functional monomer to react with acrylic acid and methyl allyl polyoxyethylene ether to prepare a polycarboxylic acid water reducer with anti-rust performance. Compared with the traditional imidazoline rust inhibitor, the rust inhibitor is grafted into the polycarboxylic acid water reducer through free radical polymerization, which solves the problem of its dispersibility. At the same time, the quaternized bisimidazoline quaternary ammonium salt also has excellent water solubility, which overcomes the disadvantage of poor water solubility of the traditional imidazoline rust inhibitor, and has excellent anti-rust effect while ensuring the water solubility of the polycarboxylic acid water reducer, and has no obvious effect on the compressive strength of the concrete itself. Different from the composite rust inhibitor prepared by the present invention, it has neither a sustained-release mechanism nor a pH-sensitive microcapsule coating, and is used for the purpose of preventing rust in the early stage of reinforced concrete; at the same time, compared with the monoquaternary ammonium salt, the bisimidazoline quaternary ammonium salt has more heterocyclic nitrogen atoms and a stronger adsorption effect on metals, and can form a protective film on the metal surface, effectively preventing the contact between the corrosive medium and the metal surface, thereby achieving the purpose of preventing metal rust.

[0032] In order to greatly extend the rust-proof ability of steel bars in reinforced concrete and improve the service life, the present invention uses intermediate B as a raw material to prepare rust-proof microcapsules with pH-sensitive sustained-release effect; the purpose is to improve the dispersibility and compatibility between the composite rust inhibitor and the modified polycarboxylic acid water-reducing agent and in concrete without affecting the compressive strength performance of the concrete itself. Intermediate B is used as a raw material and reacts with ethylene oxide through a polymerization addition reaction, and then copolymerized with styrene to prepare an amphiphilic block copolymer, and the polyether hydrophilic segment in its structure is used as the shell, and styrene and imidazoline long-chain alkyl are used as the core-shell structure. The anodic rust inhibitor sodium molybdate is coated in the microcapsule by self-assembly to prepare a composite rust inhibitor. Copolymerizing and grafting a hydrophilic polyether long chain on intermediate B and using it as a shell can solve the problem that the imidazoline rust inhibitor cannot be dissolved in water due to the presence of long-chain hydrophobic alkanes, and the cement is agglomerated and wrapped to prevent the cement from contacting with water, thereby reducing the fluidity of the cement paste. The sustained-release effect can avoid the problem of complete release and migration of rust inhibitors in the initial use of concrete, which leads to reduced rust-resistant performance of concrete in the later stage. When the pH changes from alkaline to acidic, the composite rust inhibitor slowly disintegrates, releasing the cathodic imidazoline rust inhibitor and the anodic rust inhibitor sodium molybdate in its core structure. Compared with the single rust inhibitor, the released composite rust inhibitor has a better rust-resistant effect under the same conditions, further improving the rust-resistant performance of concrete. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] In the following examples, the specification of methyl allyl polyoxyethylene ether is TPEG-2400, purchased from Nanjing Yangzi Aoke Co., Ltd.; boron trifluoride-ether complex CAS: 109-63-7, purchased from Shandong Dexin Fine Chemical Co., Ltd.; cement specification is 42.5 silicate cement, purchased from Anhui Conch Cement Co., Ltd.; coarse aggregate is limestone crushed stone with a particle size of 5-25 mm continuous grading, purchased from Tangshan Luanxian crushed stone; fine aggregate specification fineness modulus 2.92, purchased from Tangshan Luannan washed sand; fly ash was purchased from Hubei Chengfeng Chemical Co., Ltd.; the remaining raw materials are commercially available.

[0035] Preparation method of modified polycarboxylic acid water reducer: S1: 1 mol oleic acid and 2 mol formic acid are added to 50 mL toluene and stirred evenly, 20 mol hydrogen peroxide is added, heated to 80°C and refluxed for 2.5 h, 10 wt% sodium bisulfite is added, stirred for 15 min, the aqueous phase is removed, the organic phase is washed with deionized water, anhydrous sodium sulfate is added, filtered, and the solvent is removed by rotary evaporation to obtain epoxidized oleic acid;

[0036] S2: 3 g of epoxidized oleic acid, 6 g of acrylic acid, and 3.6 mg of hydroquinone were added to a reaction vessel and stirred evenly, heated to 100°C and refluxed for 6 h, ether solution was added, stirred for 15 min, the aqueous phase was removed, the organic phase was washed with saturated sodium bicarbonate solution until neutral, anhydrous sodium sulfate was added, filtered, and ether was removed by rotary evaporation to obtain acrylic oleic acid;

[0037] S3: 1 mol of epoxidized oleic acid and 1.2 mol of hydroxyethylethylenediamine are added to xylene and stirred evenly, heated to 150°C for reaction for 4 hours, heated to 220°C for reaction for 4 hours until no water is carried out, cooled to 110°C and distilled under reduced pressure to remove unreacted raw materials and xylene to obtain intermediate A; 1 mol of acrylic oleic acid and 1.2 mol of hydroxyethylethylenediamine are added to xylene and stirred evenly, heated to 150°C for reaction for 4 hours, heated to 220°C for reaction for 4 hours until no water is carried out, cooled to 110-115°C and distilled under reduced pressure to remove unreacted raw materials and xylene to obtain intermediate B;

[0038] S4: 1 mol of intermediate A, 1 mol of intermediate B, and 1 mol of dichloromethane were added to anhydrous ethanol and stirred evenly, heated to 80° C. and refluxed for reaction for 4 h, the solvent was removed by distillation under reduced pressure, and acetone was added for recrystallization and purification to obtain a bisimidazoline quaternary ammonium salt;

[0039] S5: 3 mol of acrylic acid and 0.18 mol of diimidazole quaternary ammonium salt were added to deionized water and ultrasonically dissolved to obtain solution A; 0.01 mol of ascorbic acid and 0.18 mol of thioglycolic acid were added to deionized water and ultrasonically dissolved to obtain solution B; 1 mol of methyl allyl polyoxyethylene ether was added to deionized water, heated to 70°C, stirred until the methyl allyl polyoxyethylene ether was dissolved, added with 0.014 mol of hydrogen peroxide, stirred for 10 min, and solution A and solution B were added dropwise at the same time. The reaction was kept warm for 1 h, the pH was adjusted to 7 with 40 wt% sodium hydroxide solution, the stirring was continued for 20 min, and the modified polycarboxylic acid water reducer was obtained.

[0040] The preparation method of the composite rust inhibitor comprises the following steps:

[0041] Step (1): adding intermediate B to a reaction container, adding 0.3 wt% potassium hydroxide catalyst, sealing the reaction container, introducing part of ethylene oxide until the pressure in the reaction container reaches 0.2 MPa, heating to 120° C. for reaction, continuously adding remaining ethylene oxide during the reaction, maintaining the pressure and temperature in the reaction container stable during the reaction, and heat-insulating and aging for 30 minutes after the reaction is completed to obtain an imidazoline macromonomer; wherein the molar ratio of intermediate B to ethylene oxide is 1:60;

[0042] Step (2): under a nitrogen atmosphere, 1 g of imidazoline macromonomer and 4.5 g of styrene were added to toluene and stirred evenly, 0.3 wt % of boron trifluoride-ether complex was added, and the mixture was kept at 20° C. for polymerization for 24 h, the product was washed with heptane, and vacuum dried to obtain an amphiphilic block copolymer;

[0043] Step (3): Add 2.5 g of the amphiphilic block copolymer and 4.5 g of sodium molybdate into 400 mL of 1,4-dioxane and stir for 4 h. Place the solution in a dialysis bag and seal it. Place the dialysis bag in a 1 g / L sodium molybdate solution for dialysis to obtain a composite rust inhibitor.

[0044] Example 1: A concrete additive comprises the following components in parts by weight: 15 parts of modified polycarboxylic acid water-reducing agent, 5 parts of sodium dodecyl sulfate, 1 part of composite rust inhibitor, and 50 parts of water.

[0045] Example 2: A concrete additive comprises the following components in parts by weight: 20 parts of modified polycarboxylic acid water-reducing agent, 7 parts of sodium dodecyl sulfate, 5 parts of composite rust inhibitor, and 50 parts of water.

[0046] Example 3: A concrete additive comprises the following components in parts by weight: 30 parts of modified polycarboxylic acid water-reducing agent, 9 parts of sodium dodecyl sulfate, 10 parts of composite rust inhibitor, and 50 parts of water.

[0047] Comparative Example 1: Preparation method of polycarboxylic acid water reducer: 3 mol of acrylic acid and 0.18 mol of allyltrimethylammonium chloride were added to deionized water for ultrasonic dissolution to obtain solution A; 0.01 mol of ascorbic acid and 0.18 mol of thioglycolic acid were added to deionized water for ultrasonic dissolution to obtain solution B; 1 mol of methyl allyl polyoxyethylene ether was added to deionized water, heated to 70°C, stirred until the methyl allyl polyoxyethylene ether was dissolved, 0.014 mol of hydrogen peroxide was added, stirred for 10 min, and solution A and solution B were added dropwise at the same time. The reaction was kept warm for 1 h, the pH was adjusted to 7 with 40 wt% sodium hydroxide solution, stirring was continued for 20 min, and the modified polycarboxylic acid water reducer was obtained.

[0048] A concrete additive comprises the following components in parts by weight: 15 parts of modified polycarboxylic acid water-reducing agent, 5 parts of sodium dodecyl sulfate, 1 part of composite rust inhibitor and 50 parts of water.

[0049] Comparative Example 2: Preparation method of polycarboxylic acid water reducer: 3 mol of acrylic acid and 0.18 mol of sodium methyl propylene sulfonate were added to deionized water for ultrasonic dissolution to obtain solution A; 0.01 mol of ascorbic acid and 0.18 mol of thioglycolic acid were added to deionized water for ultrasonic dissolution to obtain solution B; 1 mol of methyl allyl polyoxyethylene ether was added to deionized water, heated to 70°C, stirred until the methyl allyl polyoxyethylene ether was dissolved, 0.014 mol of hydrogen peroxide was added, stirred for 10 minutes, and solution A and solution B were added dropwise at the same time. The reaction was kept warm for 1 hour, the pH was adjusted to 7 with 40 wt% sodium hydroxide solution, stirring was continued for 20 minutes, and the modified polycarboxylic acid water reducer was obtained.

[0050] A concrete additive comprises the following components in parts by weight: 15 parts of modified polycarboxylic acid water-reducing agent, 5 parts of sodium dodecyl sulfate, 1 part of composite rust inhibitor and 50 parts of water.

[0051] Comparative Example 3: A method for preparing a composite rust inhibitor, step (1): adding intermediate B to a reaction container, adding 0.3 wt % potassium hydroxide catalyst, sealing the reaction container, introducing part of ethylene oxide until the pressure in the reaction container is 0.2 MPa, heating to 120° C. for reaction, continuously adding the remaining ethylene oxide during the reaction, maintaining the pressure and temperature in the reaction container stable during the reaction, and heat-insulating and aging for 30 minutes after the reaction is completed to obtain an imidazoline macromonomer; wherein the molar ratio of intermediate B:ethylene oxide is 1:60;

[0052] Step (2): under a nitrogen atmosphere, 1 g of imidazoline macromonomer and 4.5 g of styrene were added to toluene and stirred evenly, 0.3 wt % of boron trifluoride-ether complex was added, and the mixture was kept at 20° C. for polymerization for 24 h, the product was washed with heptane, and vacuum dried to obtain an amphiphilic block copolymer;

[0053] Step (3): Add 2.5 g of the amphiphilic block copolymer and 4.5 g of benzotriazole into 400 mL of 1,4-dioxane and stir for 4 h. Place the solution in a dialysis bag and seal it. Place the dialysis bag in a 1 g / L sodium molybdate solution for dialysis to obtain a composite rust inhibitor.

[0054] A concrete additive comprises the following components in parts by weight: 15 parts of modified polycarboxylic acid water-reducing agent, 5 parts of sodium dodecyl sulfate, 1 part of composite rust inhibitor and 50 parts of water.

[0055] Comparative Example 4: A method for preparing a composite rust inhibitor, step (1): adding intermediate B to a reaction container, adding 0.3 wt % potassium hydroxide catalyst, sealing the reaction container, introducing part of ethylene oxide until the pressure in the reaction container is 0.2 MPa, heating to 120° C. for reaction, continuously adding the remaining ethylene oxide during the reaction, maintaining the pressure and temperature in the reaction container stable during the reaction, and heat-insulating and aging for 30 minutes after the reaction is completed to obtain an imidazoline macromonomer; wherein the molar ratio of intermediate B:ethylene oxide is 1:60;

[0056] Step (2): 2.5 g of imidazoline macromonomer and 4.5 g of sodium molybdate are mixed evenly to obtain a composite rust inhibitor.

[0057] A concrete additive comprises the following components in parts by weight: 15 parts of modified polycarboxylic acid water reducer, 5 parts of sodium dodecyl sulfate, 1 part of composite rust inhibitor, and 50 parts of water.

[0058] Experiment: A kind of concrete used for performance testing includes the following components by weight: 20-30 parts of cement, 100-120 parts of coarse aggregate, 60-65 parts of fine aggregate, 10-15 parts of fly ash, 15-25 parts of water, and 1-10 parts of concrete additives.

[0059] Concrete compressive strength: Tested in accordance with GB / T 50081-2019 "Standard for Experimental Methods for Physical and Mechanical Properties of Concrete".

[0060] Cement paste fluidity: tested in accordance with GB / T 8077-2000 "Test method for homogeneity of concrete".

[0061] Salt water immersion and drying experiment: Use a steel rod made of Q235 carbon steel, with a length of 100mm and a diameter of 10mm. Add NaCl in a mass of 3.5% of the mass of mixing water into the concrete. Insert the steel rod into the concrete to form 6 groups of experimental test blocks. After curing the test blocks for 7 days, put them in an oven and dry them at 80℃ for 24h. After cooling, put them in a 3.5wt% NaCl aqueous solution and soak them for 4 days. Take them out and put them in an oven and dry them at 60℃ for 3 days. This is one cycle. After three cycles, split the test blocks and test the rust accumulation rate R of the steel rods.

[0062] R=A / A0 ×100;

[0063] Among them, R is the steel bar rust accumulation rate, %; A is the steel bar rust area after 3 cycles of immersion and drying, mm 2 ; A 0 is the surface area of ​​the steel bar, 3140mm 2 .

[0064] The experimental data are shown in Table 1 below.

[0065] Table 1 Concrete additives and concrete experimental data prepared by them

[0066]

[0067] Conclusion: The concrete additive prepared by the present invention has excellent rust-proof performance, and the high-strength concrete prepared by the concrete additive has excellent compressive strength.

[0068] In Comparative Example 1, a monoquaternary ammonium salt rust inhibitor is used to replace the bisimidazoline quaternary ammonium salt to prepare a modified polycarboxylate water reducer, resulting in poor water solubility of the modified polycarboxylate water reducer, which reduces the flowability and causes inconvenience to concrete construction. The monoquaternary ammonium salt reduces the rust inhibition performance.

[0069] In Comparative Example 2, sodium methacrylic acid was used to replace the bisimidazoline quaternary ammonium salt to prepare the modified polycarboxylic acid water reducer, resulting in reduced rust resistance.

[0070] Comparative Example 3 uses benzotriazole instead of sodium molybdate to prepare the composite rust inhibitor, resulting in reduced rust inhibition performance.

[0071] In Comparative Example 4, the composite rust inhibitor is prepared by directly mixing the imidazoline macromonomer with sodium molybdate, which causes the oil-soluble rust inhibitor molecules to be unable to dissolve in water and agglomerate, resulting in reduced fluidity. The lack of a sustained release effect leads to reduced rust inhibition performance.

[0072] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A concrete additive, characterized in that: The invention comprises the following components in parts by weight: 15-30 parts of modified polycarboxylic acid water reducer, 5-10 parts of sodium dodecyl sulfonate, 1-10 parts of composite rust inhibitor, and 50-60 parts of water; The preparation method of the modified polycarboxylate water-reducing agent comprises the following steps: S1: Add epoxidized oleic acid and hydroxyethylethylenediamine to xylene, stir evenly, heat to 150-155°C to react for 4-4.5h, heat to 220-225°C to react for 4-4.5h, cool to 110-115°C, distill under reduced pressure to obtain intermediate A; add acrylated oleic acid and hydroxyethylethylenediamine to xylene, stir evenly, heat to 150-155°C to react for 4-4.5h, heat to 220-225°C to react for 4-4.5h, cool to 110-115°C, distill under reduced pressure to obtain intermediate B; S2: Add intermediate A, intermediate B and dichloromethane to anhydrous ethanol and stir evenly, heat to 80-85°C, reflux for reaction for 4-4.5h, distill under reduced pressure, and recrystallize to obtain a bisimidazoline quaternary ammonium salt; S3: Add acrylic acid and diimidazole quaternary ammonium salt to deionized water and ultrasonically dissolve to obtain solution A; add ascorbic acid and thioglycolic acid to deionized water and ultrasonically dissolve to obtain solution B; add methyl allyl polyoxyethylene ether to deionized water, heat to 70-75°C, stir until methyl allyl polyoxyethylene ether is dissolved, add hydrogen peroxide, stir for 10-15 minutes, and simultaneously drop solution A and solution B, keep warm for 1-1.5 hours, adjust pH to 6-8, continue stirring for 20-30 minutes, and cool to room temperature to obtain a modified polycarboxylic acid water reducer; The method for preparing acrylated oleic acid comprises the following steps: Add epoxidized oleic acid, acrylic acid and hydroquinone into a reaction vessel and stir evenly, heat to 100-105°C and reflux for reaction for 6-6.5h, add ether solution, stir for 15-30min, remove the aqueous phase, wash the organic phase until neutral, add anhydrous sodium sulfate, filter, and rotary evaporate to obtain acrylic oleic acid; The preparation method of epoxidized oleic acid comprises the following steps: Add oleic acid and formic acid to toluene and stir evenly, add hydrogen peroxide, heat to 80-85°C and reflux for reaction for 2.5-3h, add sodium bisulfite, stir for 15-30min, remove the aqueous phase, wash the organic phase, add anhydrous sodium sulfate, filter, and rotary evaporate to obtain epoxidized oleic acid; The preparation method of the composite rust inhibitor comprises the following steps: Step (1): adding intermediate B to a reaction vessel, adding potassium hydroxide catalyst, sealing the reaction vessel, introducing a portion of ethylene oxide until the pressure in the reaction vessel reaches 0.2-0.21 MPa, heating to 120-130° C. for reaction, continuously adding the remaining ethylene oxide during the reaction, maintaining the pressure and temperature in the reaction vessel stable during the reaction, and aging for 30-45 minutes after the reaction is completed to obtain an imidazoline macromonomer; Step (2): adding imidazoline macromonomer and styrene to toluene in a nitrogen atmosphere and stirring evenly, adding boron trifluoride-ether complex, and carrying out polymerization reaction at 20-22° C. for 24-48 hours, washing, and vacuum drying to obtain an amphiphilic block copolymer; Step (3): Add the amphiphilic block copolymer and sodium molybdate into 1,4-dioxane and stir for 4-5 hours, place the solution in a dialysis bag and seal it, and place the dialysis bag in a sodium molybdate solution for dialysis to obtain a composite rust inhibitor.

2. A concrete additive according to claim 1, characterized in that: In the preparation process of acrylated oleic acid, the mass ratio of epoxidized oleic acid to acrylic acid is 1:2; and the amount of hydroquinone added is 0.6-0.8 mg per 1 g of acrylic acid.

3. A concrete additive according to claim 1, characterized in that: In the preparation process of epoxidized oleic acid, the molar ratio of oleic acid:formic acid:hydrogen peroxide is (1-2):(2-4):(20-40).

4. A concrete additive according to claim 1, characterized in that: In the preparation process of intermediate A, the molar ratio of epoxidized oleic acid:hydroxyethylethylenediamine is 1:1.2; in the intermediate B, the molar ratio of acrylated oleic acid:hydroxyethylethylenediamine is 1:1.2; in the bisimidazoline quaternary ammonium salt, the molar ratio of intermediate A:intermediate B:dichloromethane is 1:1:

1.

5. A concrete additive according to claim 1, characterized in that: In the preparation process of the polycarboxylic acid water reducer, the molar ratio of methyl allyl polyoxyethylene ether: acrylic acid: diimidazole quaternary ammonium salt: thioglycolic acid: hydrogen peroxide: ascorbic acid is 1:(3-4):(1-1.4):(0.18-0.36):(0.014-0.017):(0.01-0.02).

6. A concrete additive according to claim 1, characterized in that: In the preparation process of the imidazoline macromonomer, the molar ratio of intermediate B:ethylene oxide is 1:

60.

7. A concrete additive according to claim 1, characterized in that: In the preparation process of the amphiphilic block copolymer, the mass ratio of imidazoline macromonomer: styrene is (1-2):4.5; in the preparation process of the composite rust inhibitor, the mass ratio of the amphiphilic block copolymer: sodium molybdate is 2.5:(4.5-5).

8. A high-strength concrete, characterized in that: The concrete additive prepared according to any one of claims 1 to 7 comprises the following components in parts by weight: 20-30 parts of cement, 100-120 parts of coarse aggregate, 60-65 parts of fine aggregate, 10-15 parts of fly ash, 15-25 parts of water, and 1-10 parts of concrete additive.

Citation Information

Patent Citations

  • Compound concrete anti-corrosion and rust-resistant agent

    CN104478286A

  • Gemini imidazoline functional monomer, imidazoline type polycarboxylic acid water reducing agent and preparation methods of gemini imidazoline functional monomer and imidazoline type polycarboxylic acid water reducing agent

    CN116425680A